EFECTOS DE LA INFESTACION POR SYSTOLE CORIANDRI (GUSSAKOVSKY) (HYMENOPTERA: EURYTOMIDAE) EN LA GERMINACIÓN Y CONTENIDO DE ACEITE DE SEMILLAS DE CILANTRO - Lamborot, L.; Paredes, F. R.; Araya, J. E.; Arretz, P.; Guerrero, M. A. (Acta Entomológica Chilena, 2022)
Evaluations of infestation by Systole coriandri and tests of germination and oil contení of fruits of coriander apparently undam aged or with 1-2 mericarps (seeds) damaged, of sam ples obtained in central Chile, demonstrated variable infestation and germ ination levels among locations. Dissecting seeds revealed 3.8-14.0% infestation levels in apparently undamaged fruits, with linear correlation coefficients (r) of -93.4 betw een infestation and germ ination; fruits with one dam aged mericarp presented an r coefficient of -94.0 between these param eters. Fruits with both mericarps dam aged did not present germ ination, dem onstrating that S. coriandri larvae, dam age the embryo. A lso, damage to 1 or 2 m ericarps reduced oil content by 16.7 and 42.0%, respectively, from the levels in fruits apparently undamaged.